2020
DOI: 10.1017/jfm.2020.786
|View full text |Cite
|
Sign up to set email alerts
|

Ionization and dissociation effects on boundary-layer stability

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 85 publications
(145 reference statements)
1
8
0
Order By: Relevance
“…When working with the CNE assumption, the non-equilibrium is assumed to be restricted to the boundary layer, letting the inviscid region be frozen. This assumption is based on the observations made for a Mach 45 wedge in CNE [21]. Despite the high post-shock temperatures, the flow high speed renders the chemical activity considerably slower than the flow, and therefore justifies the frozen flow assumption.…”
Section: Inviscid Regionmentioning
confidence: 99%
See 3 more Smart Citations
“…When working with the CNE assumption, the non-equilibrium is assumed to be restricted to the boundary layer, letting the inviscid region be frozen. This assumption is based on the observations made for a Mach 45 wedge in CNE [21]. Despite the high post-shock temperatures, the flow high speed renders the chemical activity considerably slower than the flow, and therefore justifies the frozen flow assumption.…”
Section: Inviscid Regionmentioning
confidence: 99%
“…The inviscid flow region is characterized by the considered geometry: in the present work only flows over wedges are studied. The wedge shock jumps are obtained from the oblique jump-shock relations, consistently with the employed flow assumption, as detailed in Miró Miró et al [21].…”
Section: Inviscid Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have observed that derivatives of the MUTATION ++ properties numerically reconstructed exhibit a noisy behaviour, which is found to greatly impact the stability results. The equilibrium composition is obtained from the DEKAF boundary layer solver (Groot et al 2018), which solves the equilibrium system based on partial pressure (Miró Miró et al 2018) while enforcing the ambipolar condition. Transport properties are obtained similarly to Scoggins & Magin (2014): using approximations to Chapman and Enskog's expansion using Laguerre-Sonine polynomials following .…”
Section: Base Statementioning
confidence: 99%